Investigasi Interleaved Boost Converter menggunakan kontrol state feedback untuk pengisian baterai - Islam, Muh Izzul; Wiryajati, I Ketut; Satiawan, I Nyoman Wahyu (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the performance of the Interleaved Boost Converter (IBC) in battery charging applications using three control methods: Open loop, PID, and State feedback. The introduction highlights the importance of stability and efficiency in battery charging to enhance battery life and performance. Simulations were conducted to evaluate the system's response to each control method. The Open loop method produced an output voltage of 35V with a fast response time of 24.036 ms but suffered from significant ripple. PID control improved stability with a lower overshoot (0.248%) but slower response time (26.730 ms), and the ripple remained visible. The State feedback method, especially with a matrix gain of K2 = [-1 10 15], yielded the best performance, achieving the fastest response time of 4.779 ms, an overshoot of 0.497%, and no ripple in the output voltage. Based on these results, State feedback control is recommended for battery charging applications requiring stable and efficient voltage. PID control can be an alternative but requires further tuning for optimal performance.